Impersonal revolt. Blanchot’s Sisyphus and the erosion of the absurd man (ALPHA. Journal of Arts, Literature and Philosophy, 2017)
In the mid-20th century, Blanchot developed a thorough critique of some of Camus’ topics. His interest mainly focused on the renewal of the camusian cogito synthesized in the formula “I rebel, therefore we are.” For Blanchot, the hapless man (which constitutes the starting point for Camus’ “absurd man”) has lost the power to say “I” and is thus a figure of the impersonal that cannot be redirected to the person. Nevertheless, this does not entail a waiver of rebelliousness: Blanchot recovered the figure of Sisyphus to show that there is a rebellion of the impersonal that exceeds man, indicating the way to the “resistance of the neutral” to be claimed by French and Italian philosophy of the 21st century.
Keywords: Blanchot; Camus; impersonal; rebellion